2023
DOI: 10.1007/s00381-023-06086-w
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive hemicraniectomy in pediatric malignant arterial ischemic stroke: a case-based review

Abstract: Purpose Malignant stroke is a life-threatening emergency, with a high mortality rate (1–3). Despite strong evidence showing decreased morbidity and mortality in the adult population, decompressive hemicraniectomy (DCH) has been scarcely reported in the pediatric stroke population, and its indication remains controversial, while it could be a potential lifesaving option. Methods and results We performed an extensive literature review on pediatric malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…For instance, the RESCUEicp trial assessed 408 patients aged 10-65 years with TBI and increased ICP and found that usage of decompressive craniectomy would increase the number of survivors and percentage of individuals being independent at home after the procedure [ 10 ]. Signs of brain herniation and anisocoria are clear indications for the usage of decompressive craniectomy, and the procedure has shown promise as a treatment option for increased ICP after a pediatric TBI [ 10 , 11 ]. Temporal lobectomy may serve as an additional surgical intervention to help combat progressively increasing ICP after a severe TBI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the RESCUEicp trial assessed 408 patients aged 10-65 years with TBI and increased ICP and found that usage of decompressive craniectomy would increase the number of survivors and percentage of individuals being independent at home after the procedure [ 10 ]. Signs of brain herniation and anisocoria are clear indications for the usage of decompressive craniectomy, and the procedure has shown promise as a treatment option for increased ICP after a pediatric TBI [ 10 , 11 ]. Temporal lobectomy may serve as an additional surgical intervention to help combat progressively increasing ICP after a severe TBI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%